New insight into the role of a combination of zinc oxide and turmeric rhizome liquid extract in osteogenic marker expression - Jennifer Widjaja; Indeswati Diyatri; Wibi Riawan; Astari Puteri; Asti Meizarini (Wolters Kluwer Medknow Publications, 2021)
Aim: This research was aimed to determine the potential for treating osteogenesis with a combination of zinc oxide and turmeric (ZOT) rhizome liquid extract. Setting and Design: In vivo, post test-control group design. Material and Methods: The mandibular incisors of Wistar rats were extracted and left untreated or received an application of zinc oxideeugenol (ZOE) 10% or ZOT rhizome liquid extract at various concentrations (10%, 20%, and 40%). The mandible was then subjected to immunohistochemical analysis to detect RUNX2 and alkaline phosphatase (ALP) activity. Statistical Analysis Used: One-way ANOVA and Tukey HSD using SPSS software. Results: All groups demonstrated increasing RUNX2 and ALP activity. ZOT 40% showed the highest activity in all groups on day 3 and day 7, although there were no significant differences with ZOE 10%. Conclusion: A combination of ZOT rhizome liquid extract can induce the osteogenic process in postextraction sockets. The results highlight the need for further investigation of the potential osteogenesis of curcumin in humans.